2016
DOI: 10.3389/fpsyg.2016.01677
|View full text |Cite
|
Sign up to set email alerts
|

Personality Development during Teacher Preparation

Abstract: Objective: The purpose of this 3-year longitudinal study was to examine pre-service teachers’ personality trajectories as measured by the IPIP Big-Five factor markers during teacher preparation. The relationship between students’ personality traits, social desirability, and prior academic attainment was also examined.Method: This 3-year longitudinal study invited participants from the first year of a 4-year undergraduate (UG) pre-service teacher education program, the class of 2017. The sample consisted of 305… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 80 publications
1
15
0
3
Order By: Relevance
“…Agreeableness is not significant among teachers and students' perceptions. Corcoran and O'Flaherty (2016), who concluded that agreeableness is negatively associated with teacher personality, have similar results while Chu (2003) explains that modest correlations with the agreeable trait. Job (2004) describes a feeble undesirable correlation with kindness trait (r = -0.04).…”
Section: Discussionmentioning
confidence: 79%
“…Agreeableness is not significant among teachers and students' perceptions. Corcoran and O'Flaherty (2016), who concluded that agreeableness is negatively associated with teacher personality, have similar results while Chu (2003) explains that modest correlations with the agreeable trait. Job (2004) describes a feeble undesirable correlation with kindness trait (r = -0.04).…”
Section: Discussionmentioning
confidence: 79%
“…An additional rationale for our hypothesis is the fact that many studies showed the influence of the Big Five personality traits on the efficiency of various professional activities including those of kindergarten teachers (e.g., Corcoran & O'Flaherty, 2016). On the other hand, associations of the Dark Triad and the Big Five personality traits were found (e.g., Huang & Liang, 2015;Kornilova & Chumakova, 2016;Kowalski, Vernon, & Schermer, 2016).…”
mentioning
confidence: 88%
“…Religion, Werte) oder dispositionelle (z. B. Talente, Coping) Einflüsse stabil sein [14,15]. Charakteristische Einflussgrößen auf die Persönlichkeit sind sowohl Dimensionen des Big-Five-Modells mit Neurotizismus, Extraversion, Offenheit für Erfahrungen, Verträglichkeit sowie Gewissenhaftigkeit als auch Motive, Ziele, Pläne, Werte, Selbstbilder und Coping [16].…”
Section: Hintergrund Und Fragestellungunclassified